(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
This paper briefly presents hypotheses about gender, number and ergativity in Hittite. Terminological problems about ‘gender’ in Hittite will be sketched in the first part. ‘Gender’ is a pertinence only of core arguments and is basically visible in the contrast between a class of NPs treated with an accusative system and a defective class of NPs resulting in an ergative system (but without an ergative case). Finally the paper puts forward the hypothesis that the reason for the split in the system is to be searched in features that characterize lexical and grammatical morphemes involved in the constitution of NPs. The distribuiton of these features (basically connected to a pluralizer function pl* and a quantificational filter num) might be responsible for resorting to nt- derived nominals. KEYWORDS: Hittite, IE morphosyntax, ergative, ergativity, nominal definiteness